2002
DOI: 10.1097/00006534-200203000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Distraction in Neonates: A Strategy to Avoid Tracheostomy

Abstract: Over the past 5 years, the authors developed an application of mandibular distraction osteogenesis to eliminate existing tracheostomy. That experience led the authors to attempt mandibular distraction osteogenesis in neonates as an alternative before tracheostomy. Success with this approach using supporting objective airway measurements has been reported previously. This report includes six neonates diagnosed with Pierre Robin sequence. Of the six, five neonates ranging in age from 6 to 26 days (mean, 14.5 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(86 citation statements)
references
References 16 publications
0
81
1
4
Order By: Relevance
“…Various studies have reported on mandibular distraction for the treatment of airway obstruction and possibly avoiding tracheostomy 1618. Mandibular distraction can help correct micrognathia; by pulling the jaw forward, the tongue is pulled anteriorly via its anterior attachment to the mandible, thereby relieving the airway obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported on mandibular distraction for the treatment of airway obstruction and possibly avoiding tracheostomy 1618. Mandibular distraction can help correct micrognathia; by pulling the jaw forward, the tongue is pulled anteriorly via its anterior attachment to the mandible, thereby relieving the airway obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were able to decannulate her at 7 months of age. Since literature demonstrates that the average age of decannulation for children with Robin sequence is 3.1 years, it is possible that the distraction did shorten her tracheotomy time [25]. …”
Section: Discussionmentioning
confidence: 99%
“…When the airway is compromised because of severe mandible underdevelopment, jaw-positioning appliances [9], nasopharyngeal airway [10], orthodontic plates with velar extension [11], intubation [12], tongue-lip adhesion [13], continuous positive airway pressure (CPAP) [14], tracheostomy [15], mandibular advancement with orthognathic surgery/distraction osteogenesis [16, 17], or an anterior mandibular positioning device is used to manage the airway obstruction [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…To avoid tracheostomies, distraction osteogenesis of the mandible (surgical lengthening of the mandible) has recently been recommended as a viable option for pediatric patients with upper airway obstruction due to mandibular deficiency [16]. This technique has been described as an alternative to tracheostomy in neonates (6 to 26 days of age) to improve airway and breathing [17]. …”
Section: Introductionmentioning
confidence: 99%